Determinación de la mejor alternativa para el control químico de la piñita [Murdannia nudiflora L. Brennan] enla etapa de pre emergencia del cultivo de maíz [Zea mays (L)] en la zona de mocache. - Baños Coello, Abel Cristobal (2013)
This research was carried out on the farm "La Maria" UTEQ, Mocache – Los Ríos in 2011, located at Km 7 via Quevedo – El Empalme. Geographic coordinates are 79 ° 29 '30 "west longitude and 01 ° 10' 30" South Latitude, 120 meters above sea level. The study was conducted based on the evaluation of the best alternative to chemical control of piñita, in different doses and types of active ingredients, was used to design randomized complete block (RCB) with ten treatments and four replications mean comparison test was used Tukey. The following variables were evaluated: Incidence and severity of piñita, plant height, height of insertion of the first pod, days to flowering male and female, weighing 500 grains, yield expressed in kg / ha and economic analysis was performed treatments. It raised the overall objective: Determine an alternative to chemical control "piñita" [Murdannia nudiflora (L)], in the cultivation of corn during the pre-emergence Mocache area and specific objectives: to determine the efficient dose combinations of herbicides under study; Establish more effective alternative to chemical control "piñita" in growing corn Perform economic analysis of the study treatments. Subject to the hypothesis: At least one of the combinations of herbicides have an efficient control of the piñita [M. nudiflora (L.) Brennan]. The best control was obtained by the treatment piñita 1: Igran 500 FW 18.75 cc + Pendimetalin 50 cc + Ranger 50 cc, with 89.58% of control in relation to the first data collection, while the tallest plants and therefore the greater height of the first pod insertion introduced treatment 7: Igran 500 FW 18.75 cc + Ranger 50 cc with 2.10 m high and 1.39 m plant height of first pod insertion, showing a difference up to 40 cm in relation to treatment presented the lowest plant height, while the insertion of the first pod showed a difference of 17 cm in relation to the lower ear insertion height, the treatments were higher in male flowering precocity were: Igran 500 FW 18.75 cc + Ranger 50 cc and Igran 500 FW 18.75 cc + pendimetalin 50 cc + Ranger 50 cc. with 57.75 days showing a difference of two days in relation to treatments Igran 500 FW 12.50 + Dual Gold 12.50 cc + Ranger 50 cc e Igran 500 FW 18.75 + Dual Gold 18.75 cc + Ranger 50 cc with 59.75 days to flowering male, while the female flowering collected 1.5 days apart in relation to the treatment he got as many days. The greater weight of 500 grains scored what treatment 1: Igran 18.75 FW 500 cc + pendimetalin 50 cc + Ranger 50 cc showing weighs 181.30 g while the lower weight treatment recorded Igran 500 FW 12.50 cc + Dual Gold 12.50 + Ranger 50 Cc cc with 93.53 g having a difference of 87.77 g between treatments, the best performance kg / ha was obtained by the treatment 1: Igran 500 FW 18.75 cc + pendimetalin 50 cc + Ranger 50 cc with 8149, 90 kg while the lowest yield was recorded in the treatment 3: Igran 500 FW 12.50 + Dual Gold 12.50 cc + Ranger 50cc 4484.19 kg / ha with a difference of 3665.71 kg per hectare loss.